Development of Fort Van Der Wijck Ethnomathematics-Based Teaching Modules to Improve Middle School Students' Numeracy Skills - Khoeriah, Faridatul; Purwoko, Riawan Yudi; Wibowo, Teguh (CV. Rayyan Dwi Bharata, 2024)
This research aims to produce a teaching module product based on Fort Van Der Wijck's ethnomathematics to improve students' numeracy skills in plane material and determine the feasibility of the product in terms of validity, practicality and effectiveness. The type of research used is the research and development method (Research and Development) using the ADDIE model. The research was conducted at SMP Negeri 2 Kebumen in class VII students using a one group pretest-posttest design. Data collection techniques used are interviews, questionnaires, and tests. The research results obtained by the validity analysis from the assessment of material, media, and cultural experts obtained an average of 3.73 valid criteria. The practicality analysis of the response questionnaire obtained an average of 98.25% very positive criteria. Analysis of the effectiveness of the student learning evaluation test results with a completeness of 90% with an average score of 89.6 and an average Gain score of 0.70 or medium predicate. The results of the students' numeration ability test with 85% completeness with an average of 7.81 and an average Gain score of 0.499 or moderate predicate. These data indicate that the teaching modules developed in this study are feasible to use.